KOMPETENSI KEPEMIMPINAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER SISWA DI SMP NEGERI 4 AMUNTAI KABUPATEN HULU SUNGAI UTARA - Wahidah, Wahidah; Rabi’ah, Rabi’ah; Syahid, Akhmad Mawardi (STIT Ibnu Rusyd Tanah Grogot, 2023)
This study suggests the leadership competence of Islamic Religious Education teachers in shaping the character of students at SMP Negeri 4 Amuntai, Hulu Sungai Utara District. This study aims to determine the leadership competence of Islamic Religious Education teachers in shaping the character of students at SMP Negeri 4 Amuntai, Hulu Sungai Utara District.The subjects of this study were school principals, Islamic Religious Education teachers and students of SMP Negeri 4 Amuntai, Hulu Sungai Utara District. The object of this study is the leadership competency of Islamic Religious Education teacher of students at SMP Negeri 4 Amuntai, Hulu Sungai Utara District.Data Collection techniques from this research are using observation, interview and documentation methods. After the necessary data is obtained and collected, it is then processed using reduction teachniques, data display, and data verification. Then analyzed using descriptive qualitative method. The results of this study can be concluded that the leadership competence of Islamic Religious Education teachers in shaping the character of students at SMP Negeri 4 Amuntai, Hulu Sungai Utara Regency, Includes: First, teacher leadership competence. Islamic Religious Education in planning is to provide direction and make itself a good example and role model for students. Second, The competence of the leadership of Islamic Religious Education teacher in supporting and organizing the potential of school elements in a systematic manner, namely by always incorporating character values in each lesson and also parcipating in helping the habituation of school culture such as religious programs in schools. Third, the leadership competence of Islamic Religious Education teachers as innovators, motivators, mentors and counselors, namely by always providing advice and motivation to students to always behave well, likewise if there are students who behave deviating from the character values at scholl, they will be gaven a warning or punishment. educate student. Fourth, the leadership competence of Islamic Religious Education teachers in maintaining directing and controlling, namely by always providing direction and advice tp student, besides that PAI teachers maintain student characters with students’ parents.